Toxicity of Methylcyclohexane and Its Effect on the Reproductive System in SD Rats - Hyeon-Yeong Kim; Min-Gu Kang; Tae-Gyun Kim; Chung-Won Kang (Elsevier, 2011)
Objectives: There is limited data regarding the toxicity of methylcyclohexane, despite its wide use in rubber adhesives, paint diluents, and cleansing agents. This study aimed to verify the toxicity and influence on the reproductive system of methylcyclohexane after its repeated injection in Sprague Dawley (SD) rats. Methods: Methylcyclohexane was injected subcutaneously into male and female SD rats once a day, five times a week, for 13 weeks at different doses (0, 10, 100, and 1,000 mg/kg/day) for each group. The toxicity of testing material was verified by observing the change in body and organ weight, hematological change, pathological findings, and effect on the reproductive system at each different concentration. Results: In the 1,000 mg/kg/day group, there were cases of animal deaths. In animals that survived, hematological changes, including a decrease in the red blood cell count, were observed. A considerable weight gain or loss and pathological abnormalities in the liver, kidney, and other organs were found. However, the 10 and 100 mg/kg/day groups did not cause deaths or other specific abnormalities. In terms of reproductive toxicity, there were changes in hormone levels, including a significant decrease in hormones such as estradiol and progesterone (p < 0.001) in male animals. Menstrual cycle change for female animals did not show concentration dependency. Conclusion: When injected repeatedly for 13 weeks, methylcyclohexane proved to be toxic for the liver, heart, and kidney at a high dose. The absolute toxic dose was 1,000 mg/kg/day, while the no observed adverse effect level was less than 100 mg/kg/day. The substance exerted little influence on the reproductive system.